(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
The purpose of this study was to analyze the relationship of Emotional intelligence andCoping skills to Playing ability in Handball players at National level. The second purpose of the presentstudy was to determine the Handball Playing Ability on the basis of Emotional Intelligence and Copingskills at National level. The subjects selected for this research work in which 50 International LevelHandball players (Men) from different States of India. In the light of the experts opinion, administrativefeasibility, availability of subjects, availability of materials and also the availability of expertise forrecording the data, the following variable were selected for the purpose of this study i.e. EmotionalIntelligence, Coping Skill and Handball Playing ability. Emotional Intelligence was assessed byEmotional Intelligence Scale (EIS) constructed and standardized by Anuket Hyde, Dr. SanjyotPethe andDr. Upinder Dhar (2002). Score was the sum total of the response. Second, Athletic Coping SkillsInventory developed by Smith, Schutz, Smoll and Ptacek (1995) was used for the purpose of the presentstudy. Score was the sum total of the response The Handball Playing Ability of the subjects wasassessed by the help of three competent handball coaches used Handball Rating Scale. The scoringfrom each of the subjects was done strictly in accordance with the distribution of points as givenagainst each sub heading of the 7 components of handball playing ability.To determine the characteristics of Emotional Intelligence, Coping Skills and Handball Playing Ability ofNational level Handball Players Mean and Standard Deviation was used. In order to determine therelationship of Emotional Intelligence and Coping Skills to playing ability of Handball Players at Nationallevel, Pearson Product Moment Correlation was used. In order to predict Handball Playing Ability on thebasis of Emotional Intelligence and Coping Skills of National level Handball player, Regression Equationwas applied. The data was analyzed by using SPSS version 16.